Legitimate applications of peer to peer networks - Verma, Dinesh C. (Wiley-Interscience, 2004)
The book examines the different legitimate applications used over a peer-to-peer network (p2p)The material examines the design and development of novel applications designed to leverage the distributed nature of peer-to-peer environmentsGoes beyond the most popular application of file-sharing (including sharing of video and audio files) and discusses the many different applicationsCompares traditional and peer-to-peer infrastructure and discusses merits and demerits of each approach from a business perspective.